Destination Stewardship for Regenerative Tourism: Governance Mechanisms, Implementation Pathways, and Measurable Outcomes - I Wayan Sudiartha; Luh Putu Mahyuni; Ida Ayu Oka Martini (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Regenerative tourism addresses the limits of growth-led models, but literature remains fragmented in explaining how destination transitions are conceptualized, governed, implemented, and evaluated in practice. This study systematically reviews how destination stewardship is understood and operationalized within regenerative tourism transitions, focusing on five related questions concerning conceptualization, governance mechanisms and stakeholder arrangements, implementation pathways, measurable outcomes and indicators, and practical destination application. A Scopus-based systematic literature review of English- language, journal articles published between 2016 and 2026 was conducted, and 18 studies were included following PRISMA-based screening and eligibility assessment. The findings show that destination stewardship is emerging less as a settled concept than as a place-based, multi-actor, and restorative governance orientation. Governance is the primary operational mechanism through which regenerative transition is pursued, implementation pathways are adaptive, staged, and context-sensitive, and measurable outcomes remain the weakest part of the evidence base. Practical application is most consistently expressed through five principles: reframing destination purpose beyond growth, building governance capacity, implementing adaptively, tailoring strategy to place, and monitoring beyond conventional tourism metrics. The review contributes a review-derived analytical framework and highlights the need for clearer conceptual boundaries, stronger comparative research, and more robust destination-level regenerative indicators.